Flight Home, Flight Abroad, and International Credit Cycles - Giannetti, Mariassunta; Laeven, Luc (American Economic Review, 2012)
This paper shows that banks exhibit a weaker (stronger) home bias in the extension of new loans when funding conditions in their home country improve (deteriorate). We refer to these changes in home bias as flight abroad and flight home effects, respectively, and show that they are unrelated to the better known flight to quality effect that arises during periods of market turmoil. Our results also indicate that global banks amplify the effect of homegrown shocks on foreign countries while they are a stabilizing factor for the supply of credit in their home countries.